2010
DOI: 10.1111/j.1442-2042.2010.02670.x
|View full text |Cite
|
Sign up to set email alerts
|

Profilin 1 overexpression in renal cell carcinoma

Abstract: Objectives:To gain information about overexpressed antigens in renal cell carcinoma (RCC) by using a chemical proteomics approach. Methods: RCC cell line 769P was cultured and proteome analysis was subsequently carried out in the culture supernatants. By using sodium dodecyl sulfate-polyacrylamide gel electrophoresis (SDS-PAGE) and tandem mass spectrometry (LC-MS/MS), proteins in the culture supernatants were searched. A MEDLINE search to define the functions of the identified proteins was carried out. Results… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
21
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 28 publications
3
21
0
Order By: Relevance
“…An interesting point with respect to Pfn1 expression is similar to what Minamida et al (48) reported: we found Pfn1 overexpression in RCC tissues and cell lines. In contrast, Pfn1 has been found to be underexpressed in most, if not all, aggressive adenocarcinomas.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…An interesting point with respect to Pfn1 expression is similar to what Minamida et al (48) reported: we found Pfn1 overexpression in RCC tissues and cell lines. In contrast, Pfn1 has been found to be underexpressed in most, if not all, aggressive adenocarcinomas.…”
Section: Discussionsupporting
confidence: 91%
“…Interestingly, all 29 proteins had previously been reported to be involved in tumor progression and metastasis (Table I and supplemental Table S6). For example, two proteins that we identified as dysregulated in our study, Pfn1 and agmatinase, were also reported to have increased (48) or decreased (49,50) expression in RCC. In addition, many of the proteins we reported had been shown to be involved in cellular migration and invasion.…”
Section: Discussionmentioning
confidence: 52%
“…PFN1 was first reported as a breast cancer tumor inhibitor several years ago by Janke et al (41). Since then, PFN1 has been widely reported as a potential tumor suppressor in a variety of malignant tumors, such as skin fibrosarcoma (42), pancreatic ductal adenocarcinoma (43), hepatocellular carcinoma (44) and renal carcinoma (45). The function of PFN1 has gradually been revealed in recent years as in vitro studies on PFN1 have now been undertaken in several breast cancer cell lines.…”
Section: Discussionmentioning
confidence: 99%
“…PFN-1 expression is down-regulated in breast cancer [12], bladder cancer [24], pancreatic cancer [9], and hepatocarcinoma [22], but is overexpressed in renal cell carcinoma [15]. PFN-1 is thought to be a potent tumor suppressor in breast cancer cells [21,25].…”
Section: Introductionmentioning
confidence: 99%